Understanding and Awareness of Gender Equality in Divorce Laws in Lampung Province and Its Contribution to the Reform of Islamic Family Law in Indonesia - Hidayat, Eko; Liky Faizal; Abd. Qohar; Hilmi Yusron Rofi’i (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This article examines the understanding and awareness of gender equality in divorce cases in Lampung Province and its contribution to the reform of Islamic family law in Indonesia. The study aims to analyze the dominant factors in filing for divorce in Lampung Province, as well as the understanding and awareness of gender equality among divorce litigants from a mubādalah perspective. The research employs a qualitative method with field research. Data sources are obtained from a series of activities including interviews and observations conducted directly with judges handling divorce cases and litigants involved in divorce proceedings, complemented by secondary data from relevant scholarly works. Data analysis is performed qualitatively with a focus on the mentioned theories. The results indicate that in Lampung Province, economic factors are dominant in divorce cases, with husbands’ inability to provide for the family or wives feeling dissatisfied with the husband's provisions. The understanding and awareness of gender equality among divorce litigants are reflected in their attitudes towards women's rights, gender roles, and household division of labor, which often lead to injustice and divorce disputes. To achieve gender equality, it is recommended that changes be made to laws defining the roles of husbands and wives as mutually responsible partners in the household. This research contributes to the development of law in Indonesia by providing an in-depth analysis of the understanding and awareness of gender equality in divorce cases, particularly in Lampung Province